Processing and characterization of Arapaima gigas scales and their reinforced epoxy composites - Wendell Bruno Almeida Bezerra; Sergio Neves Monteiro; Michelle Souza Oliveira; Fernanda Santos da Luz; Fabio da Costa Garcia Filho; Luana Cristyne da Cruz Demosthenes; Ulisses Oliveira Costa (Journal of Materials Research and Technology, 2020)
The arapaima is a large Amazonian freshwater fish and an example of a natural protective system against predators such as the piranha fish. In this work, both the plain scales and a 30 vol% of arapaima scales reinforced epoxy composite were characterized for their structure, composition and morphology. The characterization was performed by scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS) and Fourier transform infrared spectroscopy (FTIR). The SEM images showed that the surface morphology of the scales was not altered by the flattening process applied before composite manufacturing. The EDS results confirm that the percentage of calcium is higher in the scale outer layer, which also shows the presence of phosphorous. The evidence of collagens in the plain scales as well as the presence of hydroxyl groups and absorption bands related to the epoxy group in the composites were revealed by FTIR. Mechanical bend tests disclosed the toughening contribution of arapaima scales to the composite epoxy matrix. Nanoindentation testing confirms the higher hardness of the scale outer layer associated with calcium participation. These experimental results provide, for the first time, an initial view of the arapaima scales potential for use as reinforcement in novel polymer composites.